Tutorial para apoio na elaboração de estudos acadêmicos de pós-graduandos do Mestrado Profissional em Tecnologia, Gestão e Saúde Ocular - Souza, Carlos Roberto De [UNIFESP] (2021)
Background: analyzing the difficulties of graduate students in preparing studies is relevant and should be a priority in the strictu sensu training period. From this perspective, Virtual Learning Environments are a reality by providing training opportunities accessible at any time and place. The emerging need to use computational techniques for rapid dissemination of knowledge and the current network infrastructure available worldwide makes it possible to use digital tools in order to overcome barriers to learning and complement the teaching and learning process. Aims: to develop a tutorial on the technical elaboration of thesis for students of the Professional Master's Degree in Technology, Management and Ocular Health at the Federal University of São Paulo. Methods: the methodological steps include a thematic scope study, literature review, adequacy and description of norms and requirements of the academic context, and creation of a tutorial to assist students of the Professional Master's Degree in Technology, Management and Ocular Health. Techniques for the preparation of studies and academic presentations were used based on the effective use of technological resources for publishing and visual didactic resources. In order to facilitate this process, Microsoft Word® and Microsoft PowerPoint® software tools were used. Results: this study showed the various forms of formatting and configuration required in an academic work based on the standards required by the Federal University of São Paulo, providing reliable guidance to graduate students from the aforementioned institution. Conclusion: the tutorial comprised stages of understanding and guidance on the structure of pre-textual, textual and post-textual elements in force in the institution's official formatting manuals, based on graphic and didactic demonstrations on the Microsoft Word® and Microsoft PowerPoint® platform.